Sex and pregnancy - Vasquez Vasquez, Javier (2015)
OBJECTIVE: To know pregnant women’s behavior with respect to sexual relations. DESIGN: Prospective study in 260 women in their immediate puerperium attended at the Obstetrics ang Ginecology Department, Loreto Regional Hospital, by an inquiry applied by two students midwifery with previous capacitation. RESULTS: 7,5% were yearold, 27,3% between 15 and 19 years, 57,3% between 20 and 35 years and 8,1% older than 35; 54% were multiparae and 40% primiparae; 92,4% started relations before age 20, 59,6% had more than 2 relations by month during the first half of pregnancy and only 34,6 during the second half. Frequency of sexual relations decreased in 87,3% compared to prepregnancy and 70% bad decreased libido; 17,7% were afraid of harming their fetus during sexual relations. In the second half pregnancy 41% preferred practicing sex lying on their side and 12,7% practiced felatio and cunnilingus; 41,2% complained of less orgasm, 24,6% masturbation during pregnancy, 11,5% bad sex during the week before delivery and 17,7 within the last month. CONCLUSIONS: Libido, frequency of sexual relations and orgasm decrease during pregnancy, changes of position occur during the second half of pregnancy. We recommend to give information on sexual relations to women of during pregnancy.